Family Attitudes Toward the Use of Technological Devices by Children During COVID-19 - Tural Büyük, Esra; Uzsen, Hatice; Koyun, Merve (Addicta: The Turkish Journal on Addictions, 2022)
This study aimed to find out the technological device using behaviors of the children and the attitudes of their families regarding this during the coronavirus disease 2019 pandemic. The study was a descriptive research composed of the mothers of 0- to 18-year-old children who were contacted through social media. Descriptive statistics of data were carried out with frequency and percentage distribution based on the demographic characteristics of the mothers. The mean age of the parents included in the study was found to be 35 ± 7 years; 89.1% were females and 31% were secondary school graduates. It was found that a techno- logical device was used by 78.1% of the children before the coronavirus disease 2019 pandemic and by 91.7% during the pandemic. Moreover, 60.2% of the children were found to have their own technological devices during the coronavirus disease 2019 pandemic including tablets in 68.8% and mobile phones in 54.9%. It was also detected that technological device usage lasted for 3–4 hours among 27.6% and for 5–6 hours among 27.9% per day; 52.3% were watching TV for 1–2 hours per day. It was determined that the rate of owning and time for using a technological device were increased during the COVID-19 pandemic.